2019
DOI: 10.3897/mycokeys.50.32432
|View full text |Cite
|
Sign up to set email alerts
|

Solving the taxonomic identity of Pseudotomentella tristis s.l. (Thelephorales, Basidiomycota) – a multi-gene phylogeny and taxonomic review, integrating ecological and geographical data

Abstract: P.tristis is an ectomycorrhizal, corticioid fungus whose name is frequently assigned to collections of basidiomata as well as root tip and soil samples from a wide range of habitats and hosts across the northern hemisphere. Despite this, its identity is unclear; eight heterotypic taxa have in major reviews of the species been considered synonymous with or morphologically similar to P.tristis, but no sequence data from type specimens have been available. With the aim to clarify the taxonomy, systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Notes. 5 th -12 th records in Finland; previous records: Parainen (1b), Lammi (2a), Ikaalinen (2a), and Ruovesi (2b) (Svantesson et al 2019) Distribution. New to Finland, and hence new to 1b (Fig.…”
Section: Pseudotomentella Sciastra Svantesson and Kõljalgmentioning
confidence: 95%
See 2 more Smart Citations
“…Notes. 5 th -12 th records in Finland; previous records: Parainen (1b), Lammi (2a), Ikaalinen (2a), and Ruovesi (2b) (Svantesson et al 2019) Distribution. New to Finland, and hence new to 1b (Fig.…”
Section: Pseudotomentella Sciastra Svantesson and Kõljalgmentioning
confidence: 95%
“…Notes. 3 rd record in Finland; previous records: Lammi (2a) and Jyväskylä (2b) (Svantesson et al 2019). Note:…”
Section: Pseudotomentella Sciastra Svantesson and Kõljalgmentioning
confidence: 98%
See 1 more Smart Citation
“…rhizopunctata ( Martini & Hentic 2003 ). Svantesson et al (2019 , 2021) described 12 new species from basidiomata previously identified as Ps. tristis , de-synonymised Ps.…”
Section: Introductionmentioning
confidence: 99%
“…This feature in combination with the texture characteristics of their basidiomata makes Pseudotomentella readily recognisable under the microscope and to the trained eye they can be identified to species group already in the field. For identification to the level of species a combination of macro- and microscopical features is often needed ( Kõljalg 1996 , Kõljalg & Larsson 1998 , Kõljalg & Dunstan 2001 , Martini & Hentic 2002 , 2003 , Svantesson et al 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%